Factors influencing the yield of transgenic mouse embryos for cryopreservation - Schwab, Anna; Schenkel, Johannes (Scandinavian journal of laboratory animal science, 2008)
Cryopreservation of pre-implantation embryos is a powerful tool to save and handle the increasing number of transgenic mouse lines, often consisting of very small populations. However, the outcome of embryos following superovulation and mating varies and is one of the limiting factors for cryopreservation. Using the data received together with the cryopreservation of more than 100,000 mouse embryos, the role of embryo yield limiting and of yield raising factors was analyzed: annual rhythms, seasonal changes (possibly due to environmental effects, such as extreme weather conditions), infections of a mouse colony, or the mating frequency of males. Then again to increase embryo yields two pheromonal effects were investigated: Especially the housing of female donors in small groups (Lee-Boot effect), but also the exposure to the future males’ bedding two days before mating (Whitten effect) resulted in remarkably higher embryo yields.